Faktor-faktor yang memengaruhi customer loyalty Shopee - Albert Mahendra Tanurahardja; Cokki Cokki (Universitas Tarumanagara, 2023)
This study aims to examine the effect of customer-perceived value and electronic service quality on customer satisfaction and customer loyalty. Then test customer satisfaction as a mediation between customer perceived value and electronic service quality on Shopee customer loyalty in Jakarta. This study used 350 samples selected by using the convenience sampling technique and then analyzed using PLS-SEM. The results of this study show customer perceived value and electronic service quality have a positive influence on customer satisfaction and customer loyalty at Shopee in Jakarta. From this study, the quality of electronic services has the greatest indirect effect on customer loyalty. This shows that Shopee must continue to maintain the quality of its electronic services and consumers’ assessment of the quality of its products and services. So that consumers feel satisfied and eventually become loyal. Penelitian ini bertujuan untuk menguji pengaruh customer perceived value dan e-service quality terhadap customer satisfaction dan customer loyalty. Kemudian, menguji customer satisfaction sebagai mediasi antara customer perceived value dan e-service quality terhadap customer loyalty Shopee di Jakarta. Penelitian ini menggunakan 350 sampel yang dipilih dengan menggunakan teknik convenience sampling dan kemudian dianalisis menggunakan PLS-SEM. Hasil dari penelitian ini adalah customer perceived value dan e-service quality memiliki pengaruh positif terhadap customer satisfaction dan customer loyalty Shopee di Jakarta. Dari penelitian ini, e-service quality memiliki pengaruh paling besar secara tidak langsung terhadap customer loyalty. Hal ini menunjukkan bahwa Shopee harus terus menjaga kualitas layanan elektroniknya dan penilaian konsumen atas kualitas produk dan jasanya. Sehingga konsumen merasa puas dan akhirnya menjadi loyal.